Political torture in popular culture: the role of representations in the post-9/11 torture debate - Adams, Alexander (Popular culture and world politics, 2016)
Introduction -- References -- Context -- The torture debate -- Camp, colony, counterterrorism -- Text -- Another Indochina -- The ticking bomb and beyond -- The war prison -- Conclusion -- Complicit -- References -- Filmography -- Index